Moral Values Of The Main Character In Little Women Movie Directed By Greta Gerwig - Tasya Rahmadona (EDUJ : English Education Journal, 2023)
This study aims to determine the meaning of the main character's moral values in the film Little Women by Greta Gerwig. Jo as the main character in this film has an optimistic personality and is a hard worker. The March sisters only live with their mother, while their father goes off to war. Circumstances demand that Jo be someone who is independent and full of responsibility. The love story that didn't go well with Laurie made Jo start honing her skills in writing in New York until she finally found her true love, Friedrich. The method of this research is descriptive qualitative research to describe the contents of the film. In this study the authors analyze the data,on how the main characters life experiences make her moral life and analyze the meaning of  moral values in the main character. The writer also finds that responsibility, pure heart, obligation and formality are the main character's moral values. In conclusion, the writer finds that Little Women contains data on moral values of five responsibilities, six pure hearts, one obligation, and three formalities.   Keywords: Moral value; movie; character